answersLogoWhite

0


Best Answer

Print "Type the upper limit (n) ?"

Input n

K = -1

WHILE K < = n

K = K + 2

Sum = Sum + K

WEND

Print "The sum of all odd numbers up to "; n; "is "; Sum

User Avatar

Wiki User

โˆ™ 2010-01-07 16:26:49
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides
๐Ÿ““
See all Study Guides
โœ๏ธ
Create a Study Guide

Add your answer:

Earn +20 pts
Q: 1 plus 3 plus 5 plus 7n how will you do this program?
Write your answer...
Submit
Related questions

How do you factor -7n squared plus 74n plus 33?

-7n2 + 74n + 33 = -7n2 + 77n - 3n + 33 = -7n*(n - 11) - 3*(n - 11) = =(-7n - 3)*(n - 11) = -(7n +3)*(n - 11)


What is 3 n plus 4 n plus 7 plus 3?

7n+10


What is n if 10n plus 3 equals 7n plus 5?

10n + 3 = 7n + 53n = 2n = 2/3


7n plus 3 equals 59 what is n?

7n + 3 = 59 7n = 56 Subtract 3 from BOTH sides n = 8 Divide by 7 on BOTH sides to isolate n


What is N if 7xN plus 3?

Simplifying 7n + 3 = 0 Reorder the terms: 3 + 7n = 0 Solving 3 + 7n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 7n = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 7n = 0 + -3 7n = 0 + -3 Combine like terms: 0 + -3 = -3 7n = -3 Divide each side by '7'. n = -0.4285714286 Simplifying n = -0.4285714286 or n = -3/7


What is the answer for (two n minus three)(n squared plus 5 n minus 1)?

It is 2n^3 + 7n^2 - 13n + 3


What is the factor of 7n2 plus 17n - 12?

(7n - 4)(n + 3)


What is the simplified form of negative 5n plus 3 open parenthesis 6 plus 7n close parenthesis?

3n + 3(6 + 7n) = 3n + 18 + 21n = 24n + 18


What is -2n plus 9n?

7n -1n,0n,1n,2n,3n,4n,5n,6n,7n 1 2 3 4 5 6 7 8 9


7 times n divided 21 equals 1 what is n?

n = 3Solution:7n/21 = 17n = 1 * 217n = 21n = 21/7n = 3


What is 3 plus 1 plus 3 plus 3 plus 3 plus 4 plus 3 plus 4 plus 1 plus 1 plus 1 plus 1 plus 1 plus 1 plus 5 plus 6?

3+1+3+3+3+4+3+4+1+1+1+1+1+1+5+6 =41 Every operation is addition so all the adding can happen in one step.


What is the total of 5 plus 6 plus 5 plus 1 plus 4 plus 1 plus 1 plus 3 plus 5 plus 4 plus 2 plus 4 plus 3 plus 1 plus 1 plus 4 plus 3 plus 4 plus 3 plus 4 plus 3 plus 1 plus 2 plus 3 plus 3 plus 1?

It is 77


What is 7nยฒ-3n equals 0?

n(7n-3) = 0 n = 0 or n = 3/7


What is 54.99 plus 3 x 1 plus 4 x 1 plus 3 x 3 plus 4 x 1 plus 3 x 1 plus 3 x 2 plus 3 x 3 plus 4 x 1 plus 3 x 1 x 3 x 3?

It is 123.99


What is 1 plus 1 plus 1 plus 1 plus 1 plus 1 plus 1 plus 1 plus 1 plus 2 plus 3 plus 3 plus 45?

it equals 62


What comes next 3 8 14 21 29?

38.The position to value rule is Un= (n2+ 7n - 2)/2 where n = 1, 2, 3, ...38.The position to value rule is Un= (n2+ 7n - 2)/2 where n = 1, 2, 3, ...38.The position to value rule is Un= (n2+ 7n - 2)/2 where n = 1, 2, 3, ...38.The position to value rule is Un= (n2+ 7n - 2)/2 where n = 1, 2, 3, ...


Translate the sum of seven times a number and three is the opposite of eighteen into an equation and solve?

7n + 3 = -18 (subtract 3 from both sides)7n + 3 - 3 = -18 - 37n = -21 (divide by 7 to both sides)n = -3


C plus plus program that will count?

#include int main (void) { puts ("1 2 3"); }


What is the nth term for 22 15 8 1 -6?

t(n) = 29 - 7n where n = 1, 2, 3, ...


What is the nth term of this sequence -2 -9 -16 -23 -30?

t(n) = 5 - 7n for n = 1, 2, 3, ... The difference between each term is -7, therefore the nth term will be: t(n) = -2 + -7 &times; (n - 1) = -2 + 7n + 7 = 5 - 7n


What is 9 plus 6 plus 4 plus 9 plus 7 plus 7 plus 6 plus 5 plus 5 plus 4 plus 3 plus 3 plus 3 plus 1 plus 1 plus 1 plus 1 plus 1 equals?

76


What is the solution to 6n-4-3 equals 3n plus 10 plus 4n?

6n - 4 - 3 = 3n + 10 + 4n -7 = 7n - 6n + 10 -17 = n


Subtract 3m-7n-12 from m -24 plus 9?

original problem: (m-24+9)-(3m-7n-12) distribute the negative sign: (m-24+9)+(-3m+7n+12) collect like terms: -2m+7n-3 that is as far as you can simplify this problem without knowing the values of m and n


Hi what is 1 plus 1 plus 2 plus 2 plus 3 plus 3 plus 3 plus 4 plus 4 equals?

23


What is the average of 3 plus 1 plus 1?

1.66666666666666666667 because 3 plus 1 plus 1 equals 5 and 5 divided by 3 equals 1.6666666666666666666.7.